2018
DOI: 10.1136/bmjopen-2017-016589
|View full text |Cite
|
Sign up to set email alerts
|

Is smoking a risk factor for tinnitus? A systematic review, meta-analysis and estimation of the population attributable risk in Germany

Abstract: ObjectiveTo assess the epidemiological association of smoking status and tinnitus with a systematic review and meta-analysis and to estimate the population attributable risk in Germany.Data sourcesA systematic literature search in PubMed and ISI-Web of Science Core Collection resulted in 1026 articles that were indexed until 15 September 2015. Additionally, proceedings of the international tinnitus seminars and reference lists of relevant articles were screened.Study selectionTwo reviewers searched independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…However, it is clear that hearing impairment is associated with tinnitus, and other well-known risk factors are noise exposure, autoimmune disorders, depression, lack of sleep, dyslipidemia, and smoking. 56 57 58 Hypertension and sleep apnea are also closely related to tinnitus. 59 60 One observation study showed that the presence of vertigo, otalgia, otorrhea, or TMJ disease can be related to tinnitus.…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, it is clear that hearing impairment is associated with tinnitus, and other well-known risk factors are noise exposure, autoimmune disorders, depression, lack of sleep, dyslipidemia, and smoking. 56 57 58 Hypertension and sleep apnea are also closely related to tinnitus. 59 60 One observation study showed that the presence of vertigo, otalgia, otorrhea, or TMJ disease can be related to tinnitus.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition to DM, smoking is also a risk factor of both early-onset cataract and tinnitus [18,33,34]. Similar to the mechanism in DM, smoking-mediated vascular dysfunction and arteriosclerosis contribute to ischaemia and hypoxia in cochlear microcirculation [35]. Moreover, hydrogen cyanide, lead, styrene and toluene in cigarette are ototoxic agents [36].…”
Section: Discussionmentioning
confidence: 99%
“…All studies which meet the inclusion/exclusion criteria will be carefully assessed with regard to the potential risk of bias by two independent assessors using the checklist developed by Downs and Black [39] and recommended in the Cochrane Handbook for Systematic Reviews of Interventions [35]. The checklist has been used previously in meta-analyses of pain-related studies, and a modified form has also been used [4042]. In our case, its contents were modified in order to apply to the type of studies which are most likely to meet the inclusion/exclusion criteria, as well as to include clinical trials and experimental studies.…”
Section: Methodsmentioning
confidence: 99%